2021
DOI: 10.1101/2021.04.24.441207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrocorticography is superior to subthalamic local field potentials for movement decoding in Parkinson’s disease

Abstract: SummarySmart brain implants will revolutionize neurotechnology for improving the quality of life in patients with brain disorders. The treatment of Parkinson’s disease (PD) with neural implants for deep brain stimulation (DBS) presents an avenue for developing machine-learning based individualized treatments to refine human motor control. We developed an optimized movement decoding approach to predict grip-force based on sensorimotor electrocorticography (ECoG) and subthalamic local field potentials in PD pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 112 publications
(250 reference statements)
0
9
0
Order By: Relevance
“…It appears to be particularly well suited for electrophysiological datasets [30], which are typically small, structured and noisy. In a recent study by Merk et al [31], XGBoost outperformed linear regression and artificial neural networks in the prediction of grip force based on STN and cortical oscillations.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…It appears to be particularly well suited for electrophysiological datasets [30], which are typically small, structured and noisy. In a recent study by Merk et al [31], XGBoost outperformed linear regression and artificial neural networks in the prediction of grip force based on STN and cortical oscillations.…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…For instance, suppressing beta while minimizing the suppression of gamma during movement might result in improved motor performance, and less stimulation induced adverse events, such as dysarthria, gait disturbances and dyskinesia. Several previous studies have demonstrated the feasibility of detecting movement state based on bioelectrical signals recorded from the cortical-basal ganglia-thalamic circuit in people PD or essential tremor (21,28,(49)(50)(51). However, extracting gamma power in real-time using chronically implanted devices might still be challenging considering stimulation artefacts.…”
Section: Remaining Challenges For the Development Of Adbs Systems For Pdmentioning
confidence: 99%
“…Using a comprehensive set of EEG features time-locked to reaching the maximum force, we could predict MV with an accuracy of around 75% in HC and around 81% in PD. These are comparable to the prediction based on features from deep brain stimulation recordings ( 29 ), but the EEG may actually be superior to subthalamic local field potentials for movement decoding in PD ( 30 ). This suggests that, under normal conditions, cortically based EEG signals may provide sufficient information to create an MV biomarker.…”
Section: Discussionmentioning
confidence: 85%